Media Framing and Stylo-Rhetorical Analysis of Selected BBC Yoruba English Premier League Related News Headline - Ridwan Akinkunmi Rabiu; Ibrahim Bamidele Onaopepo; Adetola Afolabi Ojetola; Hafsat Omolola Olawuyi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
This study conducts a content-based analysis of selected BBC Yoruba English Premier League news headlines on Meta (formerly Facebook) social media platform page. The main thrust of this research is to examine the importance of how (language use) to what (information) in new media communication. Data for this research work were gathered from BBC Yoruba news through their Meta (Facebook) page. Twenty news items were identified for analysis from the data gathered between the period of August 2022 to January 2023 of the 2022/2023 football season of the English premier league through a method of simple random sampling and were analyse within the scope of the communicative model of stylistics theory championed by Lawal (2012) and Goffmann (1974) framing media theory. The study found out that BBC Yorùbá news platform through their news headlines on English Premier League Football Clubs can be classify as a satirist who employed the use of Yorùbá language to inform, educate, entertain and banter Yorùbá English premier league football lovers. The study also revealed that out of all the verbal arts which include Slang, Adapted oral literature, Allusion, Hyperbolic-Personification, Word play and Simile adopted by BBC Yoruba, the usage of Slang is the most prominent from the list of data presented for our analysis. It was also discovered that BBC Yoruba idea of using Yorùbá language to relay English Premier League football related news is an answer to the clarion call by Yorùbá language researchers that a native approach should be adopted by all and sundry for the dissemination of information since according to Lawal (2015, p. 2) who asserts that that 80 percent of Yoruba speakers who do not speak English carry on the business of life and living on their farms and in the markets in their mother-tongue.”